Biological roles and potential applications of immune cell-derived extracellular vesicles. Issue 1 (1st December 2017) - Wen, Chuan; Seeger, Robert C.; Fabbri, Muller; Wang, Larry; Wayne, Alan S.; Jong, Ambrose Y.
ABSTRACT: Extracellular vesicles (EVs) deliver bioactive macromolecules (i.e. proteins, lipids and nucleic acids) for intercellular communication in multicellular organisms. EVs are secreted by all cell types including immune cells. Immune cell-derived EVs modulate diverse aspects of the immune system to either enhance or suppress immune activities. The extensive effects of immune cell-derived EVs have become the focus of great interest for various nano-biomedical applications, ranging from the medical use of nanoplatform-based diagnostic agents to the development of therapeutic interventions as well as vaccine applications, and thus may be ideal for 'immune-theranostic'. Here, we review the latest advances concerning the biological roles of immune cell-derived EVs in innate and acquired immunity. The intercellular communication amongst immune cells through their EVs is highlighted, showing that all immune cell-derived EVs have their unique function(s) in immunity through intricate interaction(s). Natural-killer (NK) cell-derived EVs, for example, contain potent cytotoxic proteins and induce apoptosis to targeted cancer cells. On the other hand, cancer cell-derived EVs bearing NK ligands may evade immune surveillance and responses. Finally, we discuss possible medical uses for the immune cell-derived EVs as a tool for immune-theranostic: as diagnostic biomarkers, for use in therapeutic interventions and for vaccination.